2001
DOI: 10.1080/09603120020047000
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lagrangian particle transport model to tuberculosis (TB) bacteria UV dosing in a ventilated isolation room

Abstract: The aim of this work is to define the basis for design guidelines that will minimise the risk of exposure from airborne organisms in hospital isolation rooms. This research employs an algorithm that combines an understanding of the interaction between the room airflow and the ultra violet (UV) system. The airflow in such a room is complex and therefore cannot easily be accounted for by existing design guidance. The main findings were firstly, the mean lifetime of the ventilated particles does not reduce in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The cover was attached to a rope that extended outside the chamber, and, to achieve UVGI-on conditions, the cover was removed by pulling the rope. Studies have shown that the effectiveness of an upperroom UVGI system is much more obvious at relatively low ventilation rates than at higher rates [18,19,42]. Hence, for our first experimental and numerical study for predicting the inactivation effectiveness of the UVGI system on bioaerosols, an ACH of 2.9 was used for 71 + 6% relative humidity.…”
Section: Determination Of the Decay Rates And Z-valuesmentioning
confidence: 99%
“…The cover was attached to a rope that extended outside the chamber, and, to achieve UVGI-on conditions, the cover was removed by pulling the rope. Studies have shown that the effectiveness of an upperroom UVGI system is much more obvious at relatively low ventilation rates than at higher rates [18,19,42]. Hence, for our first experimental and numerical study for predicting the inactivation effectiveness of the UVGI system on bioaerosols, an ACH of 2.9 was used for 71 + 6% relative humidity.…”
Section: Determination Of the Decay Rates And Z-valuesmentioning
confidence: 99%
“…As aerosolised microorganisms are generally very small (typically 5 μm in diameter), and can remain suspended in air for many hours, it was not considered necessary to represent them as a separate phase in the CFD model. The inactivation of microorganisms due to the UV is coupled with the scalar transport equation, as shown in Noakes et al [29] …”
Section: Cfd Model With Uv Inactivationmentioning
confidence: 99%
“…He also concluded that the number of particles removed by ventilation depends on the exhaust grille location, and that baseboard heating during winter months improves room mixing and hence UVGI e ectiveness. Alani, Barton, Seymour, and Wrobel (2001) also used a particle tracking method to determine the UV irradiation dose received by microorganisms in the presence of an upper-room UV ÿeld in a typical TB isolation room. The study demonstrated that increasing the ventilation rate does not proportionally increase the number of particles ventilated, as assumed by fully mixed models.…”
Section: Introductionmentioning
confidence: 99%